Maximum acceleration performance of professional soccer players in linear sprints: Is there a direct connection with change-of-direction ability? - Loturco, I.; Pereira, L. A.; Freitas, T. T.; Alcaraz, P. E.; Zanetti, V.; Bishop, C.; Jeffreys, I. (PLOS ONE, 2019)
The purpose of this study was to examine the selective influences of the maximum acceleration capability on change of direction (COD) speed, COD deficit, linear sprint speed, sprint momentum, and loaded and unloaded vertical jump performances in forty-nine male professional soccer players (24.3 ± 4.2 years; 75.4 ± 5.4 kg; 177.9 ± 6.4 cm). Soccer players performed the assessments in the following order: 1) squat and countermovement jumps; 2) 20-m sprinting speed test; 3) Zigzag COD ability test; and 4) bar-power outputs in the jump squat exercise. Athletes were divided, using a median split analysis, into two different groups according to their maximum acceleration rates from zero to 5-m (e.g., higher and lower ACC 0-5-m). Magnitude-based inference was used to compare the differences in the physical test results between "higher" and "lower" acceleration groups. A selective influence of the maximum acceleration ability on speed-power tests was observed, as the higher acceleration group demonstrated likely to almost certain higher performances than the lower acceleration group in all measurements (effect sizes varying from 0.66 [for sprint momentum in 20-m] to 2.39 [for sprint velocity in 5-m]). Conversely, the higher acceleration group demonstrated a higher COD deficit when compared to the lower acceleration group (ES = 0.55). This indicates compromised efficiency to perform COD maneuvers in this group of players. In summary, it was observed that soccer players with higher maximum acceleration rates are equally able to jump higher, sprint faster (over short distances), and achieve higher COD velocities than their slower counterparts. However, they appear to be less efficient at changing direction, which may be related to their reduced ability to deal with greater entry and exit velocities, or counterbalance the associated mechanical consequences (i.e., greater inertia) of being faster and more powerful.